(3efgL GdSGdc hTQYI GdfGScs - (3GdWQGHdSj GdMfaj, CHh YHO Gddg, TeS GdOjf, eMeOs ((3Ydj Hf eMeOs)
(3ChdgG (B:s
(3dc GdMeO deG bhj GdYRe HYO GdGSJNGQI Ydi ML GdHjJ hbUO GdRjGQI faK aj QhYj Gf GUfY cJGHG aj GdefGSc jchf efgGLG ddSGddc hTQYI ddefGSc GJPcQ Hg EPG CfSjJ hCgJOj Hg EPG GSoJaJjJ GbJUQ Pdc Ydi ePgH GdEeGe hGdCUMGH s
(3BNQgG (B:s
(3aEPG ONd HdOg HOC HGdeSLO ajUdj ajg QceYJjf Ef de jcf hbJ cQGgI hjONd efRdg hjbOe QLdg GdjefihjUdj aj HjJg QcYJjf dG aj hbJ GdecQhg hbO bOefG ef Pdc TjFG aj BOGH GdSaQ hcGf GdaQGZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2\1882s
(3cTa GdXfhf (B2\1882s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdabg GdMfajs